2022
DOI: 10.1186/s12876-022-02190-4
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptoms are associated with a lower risk of hospitalization and mortality and outcomes in COVID-19

Abstract: Background We aimed to find the association between gastrointestinal (GI) and respiratory symptoms with mortality and hospitalization among COVID-19 patients. Methods We analyzed the registered data of COVID-19 patients from February 20, 2020, to March 10, 2021. Depending on the patients’ disease symptoms, four categories were defined: patients with only GI symptoms, patients with only respiratory symptoms, patients with both symptoms, and patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Further, 78 studies were excluded as 61 were single‐arm studies and 17 did not provide sufficient data. Therefore, 24 comparative observational studies 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 were deemed appropriate for inclusion (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, 78 studies were excluded as 61 were single‐arm studies and 17 did not provide sufficient data. Therefore, 24 comparative observational studies 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 were deemed appropriate for inclusion (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 24 studies included in this review, 20 reported on hospitalized patients only. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 34 , 36 The remainder 14 , 33 , 35 , 37 provided data on a mixed cohort of patients including those hospitalized (in‐patients) and those not admitted (outpatients/ambulatory).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations